2022
DOI: 10.3390/v14061331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Polyclonal Antibody Developed for Serological Diagnostics of Tomato Mosaic Virus

Abstract: Plant viruses threaten agricultural production by reducing the yield, quality, and economical benefits. Tomato mosaic virus (ToMV) from the genus Tobamovirus causes serious losses in the quantity and quality of tomato production. The management of plant protection is very difficult, mainly due to the vector-less transmission of ToMV. Resistant breeding generally has low effectiveness. The most practical approach is the use of a rapid diagnostic assay of the virus’ presence before the symptoms occur in plants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…However, viral diseases have seriously affected tomato yield and quality [ 3 , 4 , 5 , 6 , 7 ], limiting global tomato trade [ 8 ]. The tomato mosaic virus (ToMV), a member of the genus Tobamovirus (family Virgaviridae ), is one of the most prevalent and devastating viruses affecting tomato production [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, viral diseases have seriously affected tomato yield and quality [ 3 , 4 , 5 , 6 , 7 ], limiting global tomato trade [ 8 ]. The tomato mosaic virus (ToMV), a member of the genus Tobamovirus (family Virgaviridae ), is one of the most prevalent and devastating viruses affecting tomato production [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five isolates of three tobamoviruses ( Table 1 ) were maintained alive in inoculated experimental plants. Virus presence in plants was tested by immunoblotting analysis using a polyclonal antibody developed for detection of tobamoviruses [ 41 ]. The symptomatic leaves from virus-positive plants were collected, sliced, mixed, and deep-frozen as a virus inoculum for subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Tobamoviruses are very stable viruses [ 11 ]. It has been shown that the tobacco mosaic virus (TMV) can remain infectious for more than 50 years outside of the host [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%